Mathematical modeling of delayed pertussis vaccination in infants - Pesco, Pablo Sebastián (2015)
Pertussisis an acute vaccine-preventable respiratory disease that remains a publichealth problem. In an attempt to improve the control of the disease, manycountries have incorporated new boosters in their vaccination schedule. Since the incorporation of these boosters is relatively recent, there are not enoughdata about their impact to support and/or universalize their use. Alternativestrategies such as the improvement in vaccine coverage and reduction invaccination delays, in addition to the incorporation of boosters, could beimplemented. Though these strategies are not new, they have not been adequatelyevaluated in order to be implemented and/or prioritized. To evaluate thepotential impact of these alternative strategies on pertussis incidence, wedeveloped a methodology that involves the use of data collected from vaccination centers and an age-structureddeterministic mathematical model for pertussis transmission. The results obtainedshow that strategies that avoid delays in vaccination have a strong impact onincidence reduction in the most vulnerable population (infants less than 1y). Inregions with high vaccination coverage (95%) the elimination of delays in thethree primary doses decreases pertussis incidence in infants by approximately20%. In regions where delays in the administration of vaccines are higher, thecombined action to reduce delays and improve coverage leads to a significantimprovement in disease control in infants. By repeating the calculations usingdifferent sets of parameters that describe different possible epidemiologicscenarios, we determined the robustness of our results. All the results presented highlight theimportance of having high vaccine coverage and shorter delays in vaccine administrationin order to reduce the impact of the disease in infants.